2001
DOI: 10.1163/156856201300194225
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin purification from human plasma in a packed-bed column system with gelatin immobilized PHEMA microspheres

Abstract: Bioaffinity chromatography has a unique and powerful role that is used as a purification tool in the production of therapeutic plasma protein derivatives. In this study, a bioaffinity-ligand, i.e. gelatin, was covalently immobilized with PHEMA microspheres (150-200 microm in diameter). The affinity sorbent carrying 7.5 mg gelatin g(-1) polymer was then used to separate fibronectin from human plasma in a packed-bed column system. Fibronectin separation from human plasma on unmodified PHEMA microspheres was 0.45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this study, we prepared a magnetic bioaffinity adsorbent carrying HSA for selective removal of bilirubin from human plasma. We selected magnetic poly(2‐hydroxyethyl methacrylate) (mPHEMA) beads as the support, which is one of the most widely used hydrophilic and biocompatible polymer in biomedical applications 22–26. When dealing with highly viscous mediums such as blood, contact with the magnetic adsorbent in a magnetically stabilized fluidized bed is desirable because of high convective transport rates without cell damage (i.e., hemolysis).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we prepared a magnetic bioaffinity adsorbent carrying HSA for selective removal of bilirubin from human plasma. We selected magnetic poly(2‐hydroxyethyl methacrylate) (mPHEMA) beads as the support, which is one of the most widely used hydrophilic and biocompatible polymer in biomedical applications 22–26. When dealing with highly viscous mediums such as blood, contact with the magnetic adsorbent in a magnetically stabilized fluidized bed is desirable because of high convective transport rates without cell damage (i.e., hemolysis).…”
Section: Introductionmentioning
confidence: 99%
“…We removed FN from the serum used in cell culture media by affinity chromatography with gelatin-sepharose 10 . After culturing cells in media containing the FN-depleted serum, we found that there was much less intracellular FN accumulation and the motility of all cortactin-manipulated cells (control, KD and rescue) was equivalent and dampened.…”
Section: Fn Is Resecreted From a Late Endosomal/lysosomal (Le/lys) Comentioning
confidence: 99%
“…p(EGDMA–HEMA–MAH)' beads were prepared by suspension polymerization of ethyleneglycol dimethacrylate (EGDMA), 2‐hydroxyethyl methacrylate (HEMA), and MAH monomers. Poly (HEMA) was selected as the basic support material, which is one of the most widely used hydrophilic polymers in biomedical applications, by considering possible applications in direct contact with plasma,12–15 in which blood compatibility is one of the main concerns 16, 17. We present the adsorption–desorption properties of HSA onto plain and Cu(II)‐chelated p(EGDMA–HEMA–MAH) beads from aqueous solutions, containing different amounts of HSA and at different pH, and also from human serum.…”
Section: Introductionmentioning
confidence: 99%